Isolation, synthesis and bioactivity evaluation of isoquinoline alkaloids from Corydalis hendersonii Hemsl. against gastric cancer in vitro and in vivo. (15th April 2022) - Luo, Tian; Li, Zhao; Deng, Xue-Mei; Jiang, Kan; Liu, Dan; Zhang, Hong-Hua; Shi, Tao; Liu, Lin-Yi; Wen, Huai-Xiu; Li, Qi-En; Wang, Zhen
Graphical abstract: Abstract: Isoquinoline alkaloid displays significant anti-gastric cancer effects due to its unique structure, which is attracting more and more attention for the development of anti-gastric cancer drugs. In this study, we explore the active components against gastric cancer from the Tibetan Medicine Corydalis hendersonii Hemsl, which is rich in isoquinoline alkaloids. 14 compounds including 2 previously undescribed natural products were obtained. Interestingly, an new active compound displays potent anti-gastric cancer activity. After accomplishing the total syntheses of the active compound and its derivatives, the anti-gastric cancer activity of the active compound was further investigated. In vitro experiments revealed that the active compound significantly attenuated the proliferative capacity, caused G2/M phase arrest, inhibited the cell migration and invasion, and induced cell apoptosis. Mechanistically, the active compound could increase the Bax/Bcl-2 ratio, elevate cytochrome c in the cytosol, and activate caspase-9/3, along with inactivating the upstream PI3K/Akt/mTOR signaling pathway. In addition, the active compound could also cause gastric cancer cell death by inhibiting topoisomerase I activity. More importantly, the anti-gastric cancer activity of the active compound was confirmed in MGC-803 xenograft nude mice in vivo . This work not only promotes the exploitation of Corydalis hendersonii Hemsl., but also provides some experience for discovering new entities from natural sources.